Screening of Chlamydia trachomatis and Waddlia chondrophila Antibodies in Women with Tubal Factor Infertility - van Dooremalen, Wies T.M. (Microorganisms, 2020)
Waddlia chondrophila is an emerging intracellular pathogen belonging to the order of Chlamydiales, and was previously associated with adverse pregnancy outcomes, as well as tubal factor infertility (TFI). In this study, we investigate the link between both W. chondrophila and Chlamydia trachomatis IgG seropositivity and TFI. Antibodies against both bacteria were measured in 890 serum samples of women visiting a fertility clinic. After a hysterosalpingography and/or laparoscopy, they were classified as either TFI-negative (TFI−) or TFI-positive (TFI+). The total seroprevalence was 13.4% for C. trachomatis and 38.8% for W. chondrophila. C. trachomatis antibodies were present significantly more often in the TFI+ group than in the TFI− group, while for W. chondrophila no difference could be observed. In conclusion, our study confirms the association between C. trachomatis seropositivity and TFI, but no association was found between W. chondrophila seropositivity and TFI. The high percentage of W. chondrophila seropositivity in all women attending a fertility clinic does, however, demonstrate the need for further research on this Chlamydia-like bacterium and its possible role in infertility.